Assessing the impact of public infrastructure on neighbourhood liveability in Cyberjaya, Malaysia: a global technological hub - Ali Komak, Foroogh; Abu Bakar, Nor Azlina; Abdul Aziz, Faziawati; Ujang, Norsidah (University of Bucharest, 2023)
The phenomenon of rapid urbanisation that has occurred since the 1950s has presented opportunities for growth and innovation in cities, primarily through the utilisation of urban agglomerations and economies of scale. Urban areas encounter diverse obstacles that restrict their ability to provide services to inhabitants and hinder the achievement of a sustainable urban future for the residents. This research examines the issue of urban functional weakness, with a specific emphasis on the emergence of a global technology hub such as Cyberjaya, Malaysia. This study analyses the relocation behaviours of the residents, with a focus on the international community, and it identifies the inadequate public infrastructure as the primary factor contributing to liveability issues within the urban area. This study employs a mixed-methods approach, utilising both quantitative data collection and in-depth interviews, to support its findings. This study examines the impact of social variables and public infrastructure on neighbourhood liveability and design quality. The findings suggest that social variables play a significant role in neighbourhood liveability, while public infrastructure has a positive effect on both liveability and design quality.